Effects of calcium and phosphorus limitation on the nutritional ecophysiology of Daphnia. (13th October 2015) - Prater, Clay; Wagner, Nicole D.; Frost, Paul C.
Abstract: Declines in environmental calcium (Ca) and phosphorus (P) concentrations have occurred over the past 30 yrs in lakes across the Canadian Shield in southern Ontario, and these reductions appear to be placing strong constraints on populations of Daphnia in this region. Here, we report results from a factorial manipulation of Ca concentrations and food P content under controlled laboratory conditions where we measured resulting changes in daphnid elemental content, individual growth and survival, and life history traits related to population growth. We found significant effects of Ca‐ and P‐limitation on all variables measured; however, dietary P explained a majority of the variation in daphnid nutrient content and growth. Dietary effects of low P [high food carbon (C): P ratios] on individual Daphnia life‐history traits also translated into significant population level effects. Dietary P also explained relatively more experimental variation in population level responses than Ca concentrations. Experimental Ca concentrations most strongly altered daphnid survival partly due to the use of a lethally low Ca concentration in our experiment. Although recent work examining shifts in zooplankton communities in this region mainly focuses on the effects of Ca‐limitation, we show that Ca concentrations and food nutrient content, at levels commonly found on the Canadian Shield, are both likely to strongly alter Daphnia life‐history and populations dynamics. Our results underscore the need to more fully examine how multielemental limitation (e.g., Ca, N, P) affects consumer physiology and life‐history given the plausible translation of these effects on the community structure of lake zooplankton.